The Effectiveness of Contextual Learning with the Small Group Discussion Method to Improve Students Critical Thinking Skills - Indahyana, Noverly; Susanti, Indri; Mahbubah, Khoiro (Jurnal Studi Guru dan Pembelajaran, 2024)
Learning in schools generally still uses conventional learning models or methods that focus on the teacher. This causes students to be less trained in critical thinking. This study aims to determine the effectiveness of implementing contextual learning with small group discussion methods to improve students critical thinking skills on environmental pollution material. The study was carried out on class X vocational students in Lamongan. This research began by conducting observations and interviews at one of the vocational schools in Lamongan Regency. The findings from the observations and interviews indicated that students have poor critical thinking skills, as traditional teaching models and methods are still being utilizedThis study employed a pre-experimental design featuring a one-group pre-test and post-test approach, with the sample selected through purposive sampling. The data in this research was obtained using the results of the pre-test and post-test given to students. A pre-test is given to students before the learning treatment is carried out using a contextual model with a small group discussion method. Post tests were given to students after learning treatment using a contextual model with small group discussion methods. The research result were analyzed using paired samples t-test and N-gain test. The results obtained from the paired sample t-test were 0.000 which showed a significant effect between learning using the contextual model with the small group discussion method to improve students critical thinking skills and was strengthened by the N-gain test for Office Management class 1 of 0.75 and the value of N-the gain of Office Management class 2 is 0.74, the N-gain value is both in the high category. So the application of contextual learning with small group discussion methods can improve students critical thinking skills.